Indirect Effects of Inflation and Monetary Tightening on Gold Prices in Indonesia: The Mediating Role of Rupiah Depreciation - Ariswati, Lusiana Desy; Filani, Libran; Aini, Rohana Nur; Raihan, Muhammad (FEB Universitas Mulawarman, 2025)
This study offers a comprehensive examination of the macroeconomic factors influencing domestic gold prices in Indonesia, emphasizing the mediating role of Rupiah exchange rate depreciation. Utilizing 70 monthly observations from January 2020 to October 2025, a timeframe marked by the COVID-19 pandemic's disruptions, supply chain challenges, and global monetary shifts, the research draws on economic principles such as the quantity theory of money and the monetary trilemma to test seven hypotheses on direct and indirect effects. Empirical results confirm strong long-run cointegration among the variables, but reveal weak short-run transmission from inflation and the BI Rate to exchange rate movements. Exchange rate depreciation emerges as a borderline statistically significant driver of gold prices, while inflation and the BI Rate are not statistically significant predictors.This pattern indicates that the limited explanatory power of inflation and the BI Rate reflects the dominance of external shocks, such as global capital flows and international monetary tightening, rather than a weakness of the empirical model itself. These findings indicate that currency dynamics, rather than domestic macroeconomic fundamentals alone, constitute the dominant transmission channel for gold price movements in Indonesia, highlighting the fragility of standard macro-financial relationships in an emerging-market context